The Effects of Fermented Rice Monascus purpureus JmbA3'K to Blood Pressure and Heart Rate Elderly Woman - Stephanus Kristianto Witono (Global Medical & Health Communication, 2018)
Incidence of hypertension is increasing rapidly, in 2000 more than 25% of the world's population of hypertension estimated in 2025 increased to 29%. The incidence of hypertension, especially in women will increase at the age of post menopause so it needs to be prevented in elderly women, especially with giving functional food that has effect to lowering blood pressure. Gamma-aminobutyric acid (GABA) is a compound that has the properties of lowering blood pressure through the regulation of smooth muscle tone of blood vessels contained in seeds fermented by Monascus purpureus sp. This research was a case control study which conducted in June 2013 to 19 women within age range 60–80 years who life in Santana Nursing Home, Cirebon to find out the influence of giving fermented rice M. purpureus JmbA3’K to systolic/diastolic blood pressure and heart rate of elderly women. Subjects were given 3 g of fermented rice M. purpureus JmbA3’K. Blood pressure and heart rate was monitored daily. The Wilcoxon signed-rank test was done to see whether the effect of giving fermented rice from the local M. purpureus JmbA3'K to the systolic and diastolic blood pressure of the elderly and the mean difference test using paired t test was done to see if the effect of fermented rice from M. purpureus JmbA3'K local to the heart rate of the elderly women. At the end of research, blood pressure and heart rate were compared before and after the treatment. At the end of the study there were no significant treatment side effects. There were improvements in aging syndrome such as: anxiety to depression, insomnia, overactive bladder (especially at night), neuralgia, and myalgia. In treatment group was found decrease in sistolic (176 to 152 mmHg) and diastolic blood pressure (90 to 83 mmHg) (p<0.05) without any changing in heart rate (81.68 to 79.32 b/sec) (p>0.05). The conclusion of this research is giving 3 grams of fermented rice M. purpureus JmbA3’K every evening meal for fourteen days decrease the sistolic and diastolic blood pressure of the elderly without any changing in heart rate.